In-plane effect on out-of-plane capacity of separated infill wall - A. Keyvani Borujeni; T. Mahdi (Numerical Methods in Civil Engineering)
In this paper, by using a finite element model, the in-plane drift effect on the out-of-plane behavior of the infilled frame with weak infill walls has been calculated. Therefore, the out-of-plane and in-plane interaction for infill walls of different slenderness/aspect ratios, bond tension strengths and separated gap types, has been evaluated. The results are shown that infill walls having full contact at the top of the wall but isolated from columns have larger out-of-plane capacities than those isolated from beam and columns. However, infill walls having full contact at the top are more vulnerable to in-plane drifts. Also, the effect of the in-plane drift on the out-of-plane capacity of the separated infill wall can be noticeable. The results are indicated the out-of-plane capacity of the separated infill wall has been found to be inversely proportional to slenderness ratio and aspect ratio values and directly proportional to bond tension strength.